PENGARUH TIPE GAYA BELAJAR TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH FISIKA DASAR II PROGRAM STUDI PENDIDIKAN FISIKA UNIVERSITAS CENDERAWASIH - Lumbu, Albert (Jurnal Ilmu Pendidikan Indonesia, 2013)
For lecturers, in terms of designing learning strategies should consider the input characteristics such as the tendency of learning styles, motivation and other factors. Therefore important for teachers to be aware of her teaching style for there is no gap between lecturers and students. For students hendanya realize the type of learning style that is owned in order to choose the most effective way of learning according to need. Has done research on the effect of learning styles on student learning outcomes in course of basic physics II on physical education courses that aim to determine the effect of learning styles on learning outcomes in student of basic physics II. The population in this study were all students of physical education courses the second semester of 2009/2010 and the force is the total sample of 31 students. Data collection techniques were observation, questionnaires and documentation. Analysis using SPSS. Results showed that learning styles possessed by students of physics education courses the second semester is a type of visual learning style. Learning styles have significant impacts on student learning outcomes with t statistic p-value of 0.000 (